(untitled) (International Journal of Built Environment and Sustainability, 2023)
Recent findings indicate Nigeria is among the top countries with devastating consequences of fire incidences. The volatile position of Port-Harcourt as an oil-producing capital city is seen as one of the reasons why fire disasters occur in hotels, among other high rises institutional building structures. This study, therefore, explored the factors responsible for the high incidences of fires in Port-Harcourt, Nigeria. As phenomenological research involving humans, a 5-point Likert scale cross-sectional questionnaire survey instruments were developed using online Google forms to evaluate people’s awareness, identify the material factors that promote fire incidents, and assess the present policy and standards to control fire incidents. The ordinal scaled data collected from 108 respondents were tested to be reliable with a Cronbach alpha of 0.958 using the SPSS Statistic software and further analyzed using the Structural Equation Modelling approach. Results show that hotel workers in Port-Harcourt are aware of fire safety management issues, though periodic retraining is required as new technologies evolve. Safety standards are also relatively maintained in the placement of equipment power points, extinguishers, and emergency controls. However, the significant causes of the fire were attributed to electrical and mechanical devices installed and utilized on the hotel premises. While the study calls for the installation of high-quality equipment in hotels, more inquiry is needed to check the reliability of individual equipment. A framework was finally conceptualized for further research and replicating the study in other contexts. This study’s findings are essential to hotel entrepreneurs and managers, fire experts, building designers, and researchers.